Dificuldades de aprendizagem relacionadas à visão: avaliação no contexto escolar com a Escala de Avaliação do Estresse Visual na Leitura pelo Professor (EEV) - Sousa, Graciele Ferreira de (2022)
This dissertation is part of the line of research on Educational Process and Teacher Training. Its main focus is the theme of visual stress (Irlen's syndrome), characterized by the presence of progressive visual discomfort and visual-perceptual distortions of the text during reading. The main objective of this study was to provide sources of evidence of content validity for the ‘Reading Visual Stress Assessment Scale by the professor’ (EEV). Its relevance to the educational area consists in the identification, through the EEV scale, of students with signs and symptoms of visual stress. As for the Method, the research is bibliographical, with a quantitative and qualitative approach. The agreement on the most relevant items to be included in the EEV was collected from seven of ten independent specialists in the area of health and education, who accepted the invitation to evaluate the scale, returning their answers by e-mail. A list with 85 items of symptoms and signs of visual stress, from six instruments, were organized in a worksheet. The experts evaluated, with a Likert scale (strongly agree, agree, not decided, disagree or strongly disagree), whether each item is a descriptor of a visual stress behaviors that can be observed by the teacher. The Content Validity Index (IVC) was used to measure the agreement between the judges regarding the representativeness of each item (minimum of 0.78) and of the instrument as a whole (minimum of 0.90). After analyzing the Results, the final version of the EEV was composed of 34 items, with an IVC as a whole of 0.94. The IVC of 15 items was 0.86 and of 19 items reached the maximum value of 1.00. Both the 20 items with a regular IVC between 0.60 and 0.77 and the 31 items with an IVC lower than 0.59 were excluded. Items were grouped into three categories: (1) general signs and symptoms of visual stress (7 items, mean IVC = 0.96); (2) difficulties with reading (22 items, mean IVC = 0.93); (3) difficulties with writing (6 items, mean IVC = 0.93). The EEV's layout and header information was changed to address the judges suggestions. For the discussion, it was considered relevant the fact it is exactly in schools, especially in the initial grades of Elementary School, that teachers perceive the first signs of failures and obstacles in reading. At the end of the present study of content validity, it was possible to elaborate the EEV, which is a standardized protocol with observational criteria of signs and symptoms of visual stress that can be recognized by teachers. After identifying the visual difficulty, the person being evaluated should be referred for a more in-depth diagnosis, with subsequent visual rehabilitation. The EEV is aligned with the Law of the Federal District 6650/2020, which provides for the adoption of tests to screen students who have visual-perceptual deficits. It was possible to conclude from the current results that the EEV has adequate content validity. Future studies should determine the cut-off score to classify the degree of intensity of visual-perceptual difficulties, as well as to prove other sources of evidence of reliability and validity.